2016
DOI: 10.3892/mmr.2016.5574
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-26a protects against cardiac hypertrophy via inhibiting GATA4 in rat model and cultured cardiomyocytes

Abstract: Pathological cardiac hypertrophy is characterized by deleterious changes developed in cardiovascular diseases, whereas microRNAs (miRNAs) are involved in the mediation of cardiac hypertrophy. To investigate the role of microRNA-26a (miR-26a) in regulating cardiac hypertrophy and its functioning mechanisms, overexpression and suppression of miR‑26a via its mimic and inhibitor in a transverse abdominal aortic constriction (TAAC)-induced rat model and in angiotensin II (Ang II)-induced cardiomyocytes (CMs) was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 30 publications
1
15
0
2
Order By: Relevance
“…Over expression of miR-26b was found to suppress GATA-4 expression by targeting the 3'-UTR, leading to increased cardiomyocyte apoptosis (51). miR-26a attenuated cardiac hypertrophy via the targeting of GATA-4 in cultured cardiomyocytes (52). Downregulation of miR-208a suppressed doxorubicin-induced cardiomyocyte apoptosis by promoting GATA-4 (53).…”
Section: Discussionmentioning
confidence: 98%
“…Over expression of miR-26b was found to suppress GATA-4 expression by targeting the 3'-UTR, leading to increased cardiomyocyte apoptosis (51). miR-26a attenuated cardiac hypertrophy via the targeting of GATA-4 in cultured cardiomyocytes (52). Downregulation of miR-208a suppressed doxorubicin-induced cardiomyocyte apoptosis by promoting GATA-4 (53).…”
Section: Discussionmentioning
confidence: 98%
“…Cardiac hypertrophy could be provoked by mechanical, neurohumoral stimuli and genetic mutation. We examined GATA4 signaling, which plays an important role in cardiomyocyte survival, vasoactive peptide-induced hypertrophic changes and maintenance of cardiac function in the adult heart [32,33], and found that expression of GATA4 in MAP4 KI mice was comparable to WT littermates at different ages (Fig. S10).…”
Section: Discussionmentioning
confidence: 99%
“…MiR-26a plays a crucial role in the regulation of cardiomyocytes (Liu et al, 2016). Huang et al found that the up-regulation of miR-26a promoted the apoptosis of hypoxia-treated H9c2 cells, while emodin (15 and 20 mM) could negatively regulate the expression of miR-26a and reduce the apoptosis by regulating miR-26a (Huang et al, 2019).…”
Section: Mir-26amentioning
confidence: 99%